Radical prostatectomy vs radiotherapy vs observation among older patients with clinically localized prostate cancer: a comparative effectiveness evaluation. (13th August 2013) - Sun, Maxine; Sammon, Jesse D.; Becker, Andreas; Roghmann, Florian; Tian, Zhe; Kim, Simon P.; Larouche, Alexandre; Abdollah, Firas; Hu, Jim C.; Karakiewicz, Pierre I.; Trinh, Quoc‐Dien
<x xml:space="preserve">Abstract</x> Objective To compare efficacy between radical prostatectomy (RP), radiotherapy and observation with respect to overall survival (OS) in patients with clinically localized prostate cancer (PCa). Methods Using data (1988–2005) from the Surveillance, Epidemiology, and End Results–Medicare linked database, 67 087 men with localized PCa were identified. The prevalence of the initial treatment strategy was quantified according to patients' life expectancy ([LE] <10 vs ≥10 years) at initial diagnosis and according to tumour stage. To reduce the unmeasured bias associated with treatment, we performed an instrumental variable analysis. Stratified (by stage and LE) Cox regression and competing‐risks regression analyses were generated for the prediction of OS and cancer‐specific mortality, respectively. Results Among patients with <10 years of LE, most were treated with radiotherapy (49%) or observation (47%). Among patients with ≥10 years of LE, most received radiotherapy (49%), followed by RP (26%). In men with <10 years of LE, RP and radiotherapy were not different with respect to OS (hazard ratio [HR]: 0.81, 95% confidence interval [CI]: 0.45–1.48, P = 0.499). Conversely, in men with ≥10 years of LE, RP was associated with an improved OS compared with observation (HR: 0.59, 95% CI: 0.49–0.71, P < 0.001) and radiotherapy (HR: 0.66, 95% CI: 0.56–0.79, P < 0.001). Similar results were recorded in competing‐risks regression analyses. Conclusion In patients with an estimated LE ≥10 years at initial diagnosis, RP was associated with improved survival compared with radiotherapy and observation, regardless of disease stage.